Assessing Awareness and Attitude of Indian Medical Students Towards Privacy and Confidentiality in Medical Practice - Bhagwat, Deepak; Kasulkar, Arti; Wakde, Shailesh (International Journal of Human and Health Sciences (IJHHS), 2025)
Background: Privacy and confidentiality are basic ethical values of medical practice. Maintaining patient trust and professional ethics requires that aspiring healthcare workers comprehend and adhere to these values. Objective: To assess the awareness and attitude of medical students regarding patient confidentiality and privacy in medical practice. Methods: This cross-sectional, descriptive study was conducted at NKP Salve Institute of Medical Sciences & Research Centre and Lata Mangeshkar Hospital, Nagpur of Maharashtra state in India, from July to December of 2024. The study population consisted of second and third year undergraduate medical students enrolled in the institute. A convenience sampling method was used, where students were invited to participate during their class hours. Medical students who consented and willing to participate were included in this study. A pretested, structured questionnaire was validated and used for data collection, which consisted of two sections: knowledge and attitude, on a 5 point Likert scale (as 1=strongly disagree to 5=strongly agree). Results: We surveyed 398 second and third-year undergraduate medical students, with 344 completing the questionnaire, resulting in a response rate of 86.43%. Of the respondents, 258(75%) believed that an implied term of the contract between a doctor and a patient constitutes professional secrecy. Additionally, 223(64.82%) students agreed that discussing a patient’s findings with third person without consent constitutes a breach of professional secrecy. A total of 226(65.69%) students agreed that a patient’s confidentiality may be breached, if the disease is contagious. Furthermore, 209(60.75%) students agreed that a doctor is legally permitted to “break” medical confidentiality, if ordered by a judge or court. 219(63.66%) students affirmed that patients are entitled to privacy and confidentiality. However, 116(33.72%) students believed that a doctor can discuss a patient’s condition with colleagues during work breaks. Conclusion: We observed that the majority of medical students demonstrated a basic awareness of privacy and confidentiality in medical practice along with positive attitude. In spite of basic awareness and positive attitude among medical students, they still require more theoretical education as well as clinically oriented ethical training. International Journal of Human and Health Sciences Vol. 09 No. 04 Oct’25 Page: 237-242